Beyond Equality of What: Sen and neutrality - Lowry, Christopher (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2009)
Based on a close reading of the debate between Rawls and Sen on primary goods versus capabilities, I argue that liberal theory cannot adequately respond to Sen’s critique within a conventionally neutralist framework. In support of the capability approach, I explain why and how it defends a more robust conception of opportunity and freedom, along with public debate on substantive questions about well-being and the good life. My aims are: (i) to show that Sen’s capability approach is at odds with Rawls’s political liberal version of neutrality; (ii) to carve out a third space in the neutrality debate; and (iii) to begin to develop, from Sen’s approach, the idea of public value liberalism as a position that falls within that third space.